KESIAPAN IBU KOTA NUSANTARA (IKN): TINJAUAN PENGARUH PENDAPATAN ASLI DAERAH DAN DANA PERIMBANGAN TERHADAP BELANJA MODAL PADA PEMERINTAH PROVINSI KALIMANTAN TIMUR - Nafisah Zulaikha Rahmalia; Shinta Permata Sari; Suhesti Ningsih (Jurnal Akuntansi dan Pajak, 2024)
This study aims to determine the effect of original income regions, general allocation funds, special allocation funds and profit sharing funds on capital expenditure of the East Kalimantan Provincial Government in 2018-2022. The method used in this study is quantitative method. The sample in this study consisted of 10 regencies/cities of East Kalimantan province. The data used is secondary data taken from the Budget Realization Report in 2018-2022 through the DJP website of the Indonesia Ministry of Finance. The results show that: (1) Local original income has effect on capital expenditure, (2) general allocation fund has effect on capital expenditure, (3) special allocation fund has no effect on expenditure capital, and (4) the profit sharing fund has effect on capital expenditure. It can be interpreted that local governments are getting better at managing its regional finances in preparing to become the capital of the archipelago.